Fluorescence lifetime imaging of red yeast Cystofilobasidium capitatum during growth - Vanek Martin; Mravec Filip; Szotkowski Martin; Byrtusova Dana; Haronikova Andrea; Certik Milan; Shapaval Volha; Marova Ivana (The EuroBiotech Journal, 2018)
Red yeast Cystofilobasidium capitatum autofluorescence was studied by means of confocal laser scanning microscopy (CLSM) to reveal distribution of carotenoids inside the cells. Yeasts were cultivated in 2L fermentor on glucose medium at permanent light exposure and aeration. Samples were collected at different times for CLSM, gravimetric determination of biomass and HPLC determination of pigments. To compare FLIM (Fluorescence Lifetime Imaging Microscopy) images and coupled data (obtained by CLSM) with model systems, FLIM analysis was performed on micelles of SDS:ergosterol and SDS:coenzyme Q with different content of ergosterol and coenzyme Q, respectively, and with constant addition of beta-carotene. Liposomes lecithin:ergosterol:beta-carotene were investigated too. Two different intracellular forms of carotenoids were observed during most of cultivations, with third form appeared at the beginning of stationary phase. Observed behavior is probably due to formation of some kind of carotenoid protective system in membranes of different compartments of yeast cell, especially cytoplasmic membrane.